Inhibition of dendritic spine extension through acrolein conjugation with α-, β-tubulin proteins. (August 2019) - Uemura, Takeshi; Suzuki, Takehiro; Ko, Kenta; Watanabe, Kenta; Dohmae, Naoshi; Sakamoto, Akihiko; Terui, Yusuke; Toida, Toshihiko; Kashiwagi, Keiko; Igarashi, Kazuei
Abstract: We have recently found that conjugation of acrolein with a 50 kDa protein(s) is strongly associated with tissue damage during brain infarction. In the current study, the identity and function of the 50 kDa protein(s) conjugated with acrolein during brain infarction were investigated. The 50 kDa protein(s) conjugated with acrolein were identified as α- and β-tubulins. Ten cysteine residues in α- and β-tubulins (Cys25, 295, 347 and 376 in α-tubulin and Cys12, 129, 211, 239, 303 and 354 in β-tubulin) were mainly conjugated with acrolein. Since two cysteine residues of α-tubulin (Cys347 and 376) and four cysteine residues of β-tubulin (Cys12, 129, 239 and 354) were located at the interaction site of α- and β-tubulins, association between α- and β-tubulins to form microtubules was strongly inhibited by conjugation with acrolein. Accordingly, dendritic spine extension consisting of microtubules was greatly inhibited in acrolein-treated Neuro2a cells. The results strongly suggest that acrolein contributes to the functional losses in brain signaling through its conjugation with α- and β-tubulins.